Assessing the universal structure of personality in early adolescence : the NEO-PI-R and NEO-PI-3 in 24 cultures - De Fruyt, F. (Array, 2009)
The structure and psychometric characteristics of the NEO Personality Inventory-3 (NEO-PI-3), a more readable version of the Revised NeO Personality Inventory (NEO-PI-R), are examined and compared with NEO-PI-R characteristics using data from college student observer ratings of 5, 109 adolescents aged 12 to 17 years from 24 cultures. Replacement items in the PI-3 showed on average stronger item-total correlations and slightly improved facet reliabilities compared with the NEO-PI-R in both English- and non-english-speaking samples. NEO-PI-3 replacement items did not substantially affect scale means compared with the original scales. Analyses across and within cultures confirmed the intended factor structure of both versions when used to describe young adolescents. The authors discuss implications of these cross-cultural findings for the advancement of studies in adolescence and personality development across the lifespan.